2013
DOI: 10.1017/s0033291713001323
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of computerized cognitive behavioural therapy for depressive symptoms: effectiveness and costs of a workplace intervention

Abstract: BackgroundDepression and anxiety are major causes of absence from work and underperformance in the workplace. Cognitive behavioural therapy (CBT) can be effective in treating such problems and online versions offer many practical advantages. The aim of the study was to investigate the effectiveness of a computerized CBT intervention (MoodGYM) in a workplace context.MethodThe study was a phase III two-arm, parallel randomized controlled trial whose main outcome was total score on the Work and Social Adjustment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 16 publications
5
97
0
Order By: Relevance
“…Participants also improved on the secondary outcomes, which sustained over time. The large improvements on depressive symptoms in the CAU group were also found in 2 studies with comparable target groups of non-sick-listed employees [28,66]. Therefore, it could be possible that spontaneous recovery of depressive symptoms is more likely in this specific target group.…”
Section: Discussionmentioning
confidence: 61%
“…Participants also improved on the secondary outcomes, which sustained over time. The large improvements on depressive symptoms in the CAU group were also found in 2 studies with comparable target groups of non-sick-listed employees [28,66]. Therefore, it could be possible that spontaneous recovery of depressive symptoms is more likely in this specific target group.…”
Section: Discussionmentioning
confidence: 61%
“…Four of the included trials provided support related to the technical aspects of the online platforms, 15,31,33,36 whereas 9 trials were purely self-guided. [12][13][14]30,32,34,35,37,38 The control conditions used were attention placebo, no treatment, treatment as usual, or waiting list. The included studies were conducted in 6 countries: Australia, Germany, Spain, Switzerland, the Netherlands, and the United Kingdom (eTable 1 in the Supplement presents a summary of study characteristics).…”
Section: Study and Participant Characteristicsmentioning
confidence: 99%
“…However, recent large trials found a range of effects, varying from small to moderate effect sizes 12,13 to no effect. 14,15 These contradicting findings drew much attention and raised concerns about the benefits of these interventions.…”
mentioning
confidence: 99%
“…Phillips et al [19] tested the effectiveness of a computerized CBT intervention (MoodGYM course developed by the Australian National University). Their study was a 2-arm, parallel randomized controlled trial with a 5-week intervention period and follow-up at 6 and 12 weeks.…”
Section: Technology Applied To (Psycho)therapy (Is It Still Psychothementioning
confidence: 99%
“…This seems obvious especially for the study of Phillips et al [19]. (This review was supported in part by the National Institute on Drug Abuse and by VINS 1 Mental Illness Research, Education, and Clinical Center.…”
Section: Technology Applied To (Psycho)therapy (Is It Still Psychothementioning
confidence: 99%